2004
DOI: 10.1016/j.physa.2004.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Stations, trains and small-world networks

Abstract: The clustering coefficient, path length and average vertex degree of two urban train line networks have been calculated. The results are compared with theoretical predictions for appropriate random bipartite graphs. They have also been compared with one another to investigate the effect of architecture on the small-world properties.Comment: 6 pages, prepared in RevTe

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
128
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(148 citation statements)
references
References 14 publications
(41 reference statements)
6
128
0
Order By: Relevance
“…Sen et al [22] concluded that India's railway network exhibited small world properties. Similar properties were reported by Seaten and Hackett [23] in a study of railway networks in Boston and Vienna. Jiang and Claramunt [24] found that the topological networks of streets exhibited small world properties but were not scale-free.…”
supporting
confidence: 87%
“…Sen et al [22] concluded that India's railway network exhibited small world properties. Similar properties were reported by Seaten and Hackett [23] in a study of railway networks in Boston and Vienna. Jiang and Claramunt [24] found that the topological networks of streets exhibited small world properties but were not scale-free.…”
supporting
confidence: 87%
“…Instead, in the resulting topology, the length of a shortest path between two arbitrary stations A and B is the number of changes of mean of transportation one needs to get from A to B [39]. This approach was used in [3,12,13]; in the latter the authors used the term space P. In space-of-stops, two stations are connected if they are two consecutive stops on a route of at least one vehicle [13]. Here the length of a shortest path between two stations is the minimal number of stops one needs to make.…”
Section: Spaces and The Difficulty Of The Problemmentioning
confidence: 99%
“…Julian Sienkiewicz [7] Topological analysis of 22 urban bus networks in Poland. Seaton and Hackett [8] calculate the complex statistical characteristics of the city train network. Domestic research, including Qian Xu [9] on the city's public transport network degree of the distribution of the situation.…”
Section: City Bus Networkmentioning
confidence: 99%